2019
DOI: 10.1111/and.13411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dioxin on testicular histopathology, sperm parameters, and CatSper2 gene and protein expression in Naval Medical Research Institute male mice

Abstract: The CatSper gene family is known to be solely expressed in sperm cells and is possibly associated with sperm motility and penetration through the zona pellucida. Despite its vital role in male fertility, factors regulating its expression are not widely known. The present study aimed at evaluating the effects of dioxin on CatSper2 gene and protein expression, testicular histopathology, sperm quality and biochemical parameters in a mice model. The experiments were performed on 32 Naval Medical Research Institute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…25,27 In addition, prenatal TCDD administration on gestational day 15 (at 0.064-1 µg/kg) demasculinized and feminized morphology of Holtzman male rat offsprings. 26 Abnormal sperm parameters and sperm viability were also reported 28,29 Spermatogenic markers (such as acid phosphatase, alkaline phosphatase, lactate dehydrogenase)…”
Section: Dioxinsmentioning
confidence: 98%
See 1 more Smart Citation
“…25,27 In addition, prenatal TCDD administration on gestational day 15 (at 0.064-1 µg/kg) demasculinized and feminized morphology of Holtzman male rat offsprings. 26 Abnormal sperm parameters and sperm viability were also reported 28,29 Spermatogenic markers (such as acid phosphatase, alkaline phosphatase, lactate dehydrogenase)…”
Section: Dioxinsmentioning
confidence: 98%
“…Testicular histology showed necrotic degeneration in dioxin exposed mice in comparison with controls. 29 Furthermore, reduced expression of steroidogenic markers such as StAR protein, 3-β-HSD, and 17-3-β-HSD was also reported suggestive of impaired steroidogenesis 28 with reduced circulating levels of both testosterone and dihydrotestosterone (DHT) in adult rats exposed to high concentrations of TCDD 30 Furthermore, TCDD suppressed the expression of glutamic acid decarboxylase 67, an enzyme involved in GABA synthesis in the brain of gestationally exposed rats, potentially preventing the perinatal surges of LH and testosterone compromising sperm counts. 31 Results from these studies suggest both an adverse endocrine effect as well as direct testicular toxicity.…”
Section: Dioxinsmentioning
confidence: 99%
“…A recent study in male mice reported a significant fall in sperm motility and count, in mice exposed to dioxin. Furthermore, on testicular histopathology, they observed necrotic degeneration and reduced epithelium thickness in mice exposed to dioxin as compared to the controls [50]. Furthermore, supporting the fact that dioxin exposure seriously affects the sperm functions in males resulting in poor quality semen and hence, male infertility.…”
Section: Exposure To Harmful Chemicalsmentioning
confidence: 81%
“…Modelli in vitro ed in vivo hanno dimostrato che i composti diossina-simili e il TCDD legano il recettore degli idrocarburi arilici (AhR), un fattore di trascrizione citoplasmatico che, in seguito a legame con il ligando e traslocazione nel nucleo, forma un complesso con l'AhR nuclear translocator (ARNT) e regola l'espressione di geni bersaglio, compresi geni estrogeno-dipendenti, esercitando, pertanto, azioni estrogeno-mimetiche che possono interferire con il sistema endocrino endogeno [19]. Inoltre, in modelli animali è stato dimostrato che il trattamento con TCDD riduce significativamente conta totale, motilità e morfologia tipica degli spermatozoi, nonché l'espressione negli spermatozoi della proteina CatSper, implicata nella regolazione della motilità e della penetrazione della zona pellucida, ed è stata documentata degenerazione necrotica del testicolo con ridotto spessore dell'epitelio seminifero, correlati all'aumento dei radicali liberi dell'ossigeno e allo stress ossidativo, mediati dalla riduzione dell'espressione di superossido dismutasi e catalasi [20].…”
Section: Diossineunclassified